1933
DOI: 10.1084/jem.58.5.513
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Recently Isolated Human Strains and a Passage Strain of Poliomyelitis Virus

Abstract: Since the early days of the discovery of the virus of poliomyelitis it has been known that quantitative differences in virulence for the monkey exist between recently isolated strains, and strains which have passed through successive monkeys. Only within the last few years has it been clearly demonstrated b y the work of Burnet and Macnamara (1) in Australia, that immunologic differences exist between such strains, which might be termed qualitative differences, in that they do not seem to be confined to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1934
1934
1943
1943

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…The failure to develop protective substances in convalescent sera from paralytic cases also coincided with the findings of Paul and Trask (19) who showed that 6 of 7 sera taken 1% to 10 weeks after the onset failed to neutralize the virus; 2 of them when retested a year later still failed to neutralize. On the other hand, Jensen (24) reported the presence of antibodies in paralytic and non-paralytic cases within a month after the onset.…”
Section: Dikcussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The failure to develop protective substances in convalescent sera from paralytic cases also coincided with the findings of Paul and Trask (19) who showed that 6 of 7 sera taken 1% to 10 weeks after the onset failed to neutralize the virus; 2 of them when retested a year later still failed to neutralize. On the other hand, Jensen (24) reported the presence of antibodies in paralytic and non-paralytic cases within a month after the onset.…”
Section: Dikcussionsupporting
confidence: 78%
“…Such findings differ from those of Howitt (22) who reported that convalescent serum more often neutralized a recently isolated strain than a passage virus. Likewise, Paul and Trask (19) found that convalescent sera from 6 of 7 paralytic cases neutralized a recently isolated strain, whereas only one serum neutralized the passage virus. It is possible that the strain used in the present work was more closely related to the passage virus than that used by the above workers (19,22) (Table I) in convalescent sera from paralytics obtained years after the disease, than was found in the present work in which the sera were collected within a year of onset.…”
Section: Dikcussionmentioning
confidence: 94%
See 3 more Smart Citations